In situ stress measurement method of deep borehole based on multi-array ultrasonic scanning technology - Wang, Jinchao; Wang, Chuanying; Huang, Junfeng; Han, Zengqiang; Zeng, Wenhao; Wang, Yiteng (Frontiers in Earth Science, 2022)
In order to improve the accuracy and efficiency of deep in-situ stress measurement, based on the wall collapse in deep borehole, a deep borehole in-situ stress measurement method based on multi-array ultrasonic scanning technology is proposed in this paper. The solution idea of using the combination of multiple elements for borehole contour scanning is put forward, and a multi-array ultrasonic scanning technology suitable for fine horizontal section scanning of deep geological borehole contour is formed. Through the analysis of the calculation principle of hole wall caving method and the derivation of multi-array element ultrasonic scanning solution algorithm, a multi-array ultrasonic scanning device is developed by using the effective fusion of multi-array ultrasonic full waveform scanning signals and the reconstruction of horizontal section contour. The measurement method of in-situ stress in deep borehole combined with hole wall caving method is studied. Finally, the feasibility and accuracy of this method are verified by physical experiments. The results show that: the effective fusion of multi-array ultrasonic full waveform scanning signals and horizontal section contour reconstruction can break through the limitations of conventional in borehole probe placement and in borehole medium sound velocity calibration, and improve the fine reconstruction and accurate measurement of 360° wall shape. The multi-array ultrasonic scanning technology can obtain the borehole shape data at any borehole depth, and then obtain the three-dimensional shape measurement of borehole wall, which can provide a new technical means for the three-dimensional detection of borehole wall and in-situ stress measurement.